Case Report: Abortus Spontan Incomplete - Agus Putu Agung (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2018)
A woman patient on behalf of NWM aged 28 years came with her husband to Community and Primary Health Care Center complaint of rupture of membranes and fetus with placenta going out at home, 3.5 hours before go to Community and Primary Health Care Centre (Puskesmas). When the incident occurred, the patient was at home, and the patient pulled the placenta by herself. The patient was not in strenuous activity, and there was no prior history of vaginal bleeding before. The patient has no fever and does not suffer any pain. The calculation of the first day of last menstruation on April 30, 2017, shows that her second pregnancy is 22 weeks old. First pregnancy miscarriage at 17 weeks' gestation. The patient suffered severe nausea and vomiting during the first semester of pregnancy and was admitted to the Puskesmas Nusa Penida I for four days with a diagnosis of hyperemic gravidarum. Patients did not immediately go to the Puskesmas because they had to bury their babies first in Setra. ........................